A167 EVALUATING THE DIAGNOSTIC YIELD OF COMPUTED TOMOGRAPHIC ENTEROGRAPHY FOR PATIENTS WITH IRON DEFICIENCY ANEMIA. (1st March 2018) - Buttar, J; Hirji, Z; Atkinson, K
Abstract: Background: Although several etiologies exist, gastrointestinal bleeding is widely considered to be responsible for Iron Deficiency Anemia (IDA). Currently, there is debate regarding the most appropriate course of investigation following negative bidirectional endoscopy. Computed Tomographic Enterography (CTE) has emerged as a prospective diagnostic tool but limited studies have outlined its role, specifically for investigation of IDA. Aims: To evaluate the efficacy of CTE through diagnostic yield for patients with IDA. Furthermore, to outline etiologies of gastrointestinal bleeding, predictive symptoms, and changes in management for true positive cases. Methods: Patients were identified by CTE requisition orders at the Royal Columbian Hospital Centre consecutively between Jan 1, 2013 and June 1, 2017. Only patients diagnosed with Iron Deficiency Anemia, or who had experienced obscure occult gastrointestinal bleeding were included. To determine the diagnostic yield of CTE, patients' charts were retrospectively studied. Negative endoscopy or lack of further small bowel investigation following a negative CTE was defined as a True Negative. Positive endoscopy for small bowel carcinomas matching the description of a prior CTE was defined as a True Positive. Results: 937 CTE results were reviewed and 223 patients matched our inclusion criteria. 7 positive CTE results were identified, 3 of which were false positives. 216 negative CTE results were identified, none of which were false negatives. Follow-up Capsule Endoscopy (CE) was used in 13 negative cases, of which 3 identified non-malignant sources of GI bleeding. The diagnostic yield of CTE was 1.8%, with 100% sensitivity and 98.6% specificity. The etiologies of the 4 positive cases included a GIST tumor, a small bowel spindle cell neoplasm, and two moderately differentiated adenocarcinomas. Further investigation included an imaging technique (Colonoscopy or Laparoscopy) followed by surgical small bowel resection. In one case, CE was used to localize the tumor within the small bowel following positive CTE. None of the symptoms exhibited by the patients of the four positive cases were atypical of diagnostic symptoms of IDA. Conclusions: CTE has high sensitivity and specificity in investigating IDA. Only 1.8% of patients had a change in management based on CTE but all were significant. The four lesions identified by CTE required further imaging, including CE, before surgical resection. Given that CE has a higher diagnostic yield than CTE, it may be a better choice for IDA if no contraindication to CE exists, as opposed to CTE followed by CE. Funding Agencies: None